2018
DOI: 10.3390/su10082711
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Difference between Indirect and Direct CO2 Emissions: Evidence from Korean Manufacturing Industries, 2004–2010

Abstract: This study measures and decomposes green productivity growth of Korean manufacturing industries between 2004 and 2010 using the Malmquist-Luenberger productivity index. We focus on differences in the measures of productivity growth by distinguishing carbon emissions from either end-user industries or the electricity generation industry. Empirical results suggest three main findings. First, the efficiency of total emissions is higher than that of direct emissions except for the shipbuilding industry. Second, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Lee et al [38] found the efficiency of total emissions is higher than that of direct emissions except for the shipbuilding industry. Almeida and Terra [39] presented that the innovation context can influence the development of enterprises, through a variety of factors, such as the institutional environment, the characteristics of the economic sector, sustainability management and established networks that affect the decision making and growth of the companies.…”
Section: Analyses Of the Resultsmentioning
confidence: 96%
“…Lee et al [38] found the efficiency of total emissions is higher than that of direct emissions except for the shipbuilding industry. Almeida and Terra [39] presented that the innovation context can influence the development of enterprises, through a variety of factors, such as the institutional environment, the characteristics of the economic sector, sustainability management and established networks that affect the decision making and growth of the companies.…”
Section: Analyses Of the Resultsmentioning
confidence: 96%
“…To assess the environmental effect of MCH dehydrogenation in an MR compared to the a conventional PBR, CFA was conducted based on the results of the techno-economic analysis. The carbon footprint is classified according to the types of processes as follows; direct carbon emissions from controlled processes like chemical reactions or heater and indirect carbon emissions from uncontrolled processes such as electricity consumed in the compressor [59]. In this study, for both a PBR and an MR, CO 2 emissions from the dehydrogenation reactor and heater (direct carbon emission) and compressor (indirect carbon emission) were considered in CFA.…”
Section: Carbon Footprint Analysis (Cfa)mentioning
confidence: 99%
“…However, if the ICT industry is the industry that causes environmental pollution due to high CO 2 emissions, then the ICT industry cannot be said to be a sustainable industry. Therefore, many researchers are continuing research to measure CO 2 emissions of each country and CO 2 emissions of major industries in order to find industries with less environmental pollution [33,[35][36][37][38][39]. Loefgren and Muller [35] studied the relationship between energy use efficiency and carbon emissions and suggested a plan to improve carbon emission efficiency as an effective method to reduce carbon emission.…”
Section: Ict Manufacturing Industrymentioning
confidence: 99%
“…Zhou et al [36] used DEA to estimate the CO 2 emission efficiency of OECD countries. Jaeger et al [39] concluded that low-carbon-based growth is optimistic for economic growth and job creation in their research Lee et al [38] conducted a study to measure the productivity of the Korean manufacturing industry based on CO 2 emissions. Moon et al [37] analyzed linkage effects of all Korean industries from 2005 to 2015 in a time series to derive eco-friendly industries with high linkage effects.…”
Section: Ict Manufacturing Industrymentioning
confidence: 99%